2013
DOI: 10.1270/jsbbs.63.116
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the clubroot resistance gene <i>CRb</i> and development of a useful selectable marker in <i>Brassica rapa</i>

Abstract: In Chinese cabbage (Brassica rapa), the clubroot resistance (CR) gene CRb is effective against Plasmodiophora brassicae isolate No. 14, which is classified as pathotype group 3. Although markers linked to CRb have been reported, an accurate position in the genome and the gene structure are unknown. To determine the genomic location and estimate the structure of CRb, we developed 28 markers (average distance, 20.4 kb) around CRb and constructed a high-density partial map. The precise position of CRb was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 25 publications
1
95
0
1
Order By: Relevance
“…2. Also, linkage analysis integrated 11 markers reported by Kato et al (2013) which co-segregated with the resistance derived from 'Mendel' with the one co-segregating marker reported by Ueno et al (2012). Thus, all 12 co-segregating markers mapped to the A3 chromosome (Fig.…”
Section: Genotypic Analysis and Mapping Of Cr In Spring Canola Derivementioning
confidence: 87%
See 3 more Smart Citations
“…2. Also, linkage analysis integrated 11 markers reported by Kato et al (2013) which co-segregated with the resistance derived from 'Mendel' with the one co-segregating marker reported by Ueno et al (2012). Thus, all 12 co-segregating markers mapped to the A3 chromosome (Fig.…”
Section: Genotypic Analysis and Mapping Of Cr In Spring Canola Derivementioning
confidence: 87%
“…The genomic DNA of the parents and the bulks were screened with 370 (212 A ? 158 C) Brassica SSR markers obtained from Agriculture and AgriFood Canada (AAFC) through a material transfer agreement, one RAPD marker (Diederichsen et al 2006), two SSR markers flanking the CR locus of A3 and two markers from C3 linkage groups of Werner et al (2008), and 72 published markers reported to be linked to the nine published CR loci: the CRa (Matsumoto et al 1998Hayashida et al 2008;Ueno et al 2012), CRb (Piao et al 2004, Zhang et al 2014, CRb Kato (Kato et al 2012(Kato et al , 2013, CRk and Crr3 (Hirai et al 2004;Saito et al 2006) on A3, CRc on A2 Matsumoto et al 2012), Crr1, Crr2 and Crr4 on A8, A1 and A6, respectively (Suwabe et al 2003. For convenience of reference to the molecular markers and discussion, the locus reported by Kato et al (2012Kato et al ( , 2013 will be referred hereafter as CRb Kato .…”
Section: Dna Extraction Pcr Amplification and Electrophoresismentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies reported the phenomenon of sub-genome dominance among the three sub-genomes in Brassica s 8,9 , and found that the biased distribution of small RNA-targeted TEs plays an important role in this phenomenon 11,12 . Furthermore, the release of the genome sequences has also contributed to the mapping, cloning and functional studies of agronomic genes in Brassica crops, such as two clubroot resistance genes 13,14 , two blackleg resistance genes 15,16 , as well as two key genes regulating the time of flowering 17–19 . The availability of these reference genomes also made it possible to build variome datasets by resequencing populations of B. rapa and B. oleracea , to investigate domestication of the diverse morphotypes.…”
Section: Background and Summarymentioning
confidence: 99%